2003
DOI: 10.2165/00007256-200333030-00002
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nonsteroidal Anti-Inflammatory Drugs Following Exercise-Induced Muscle Injury

Abstract: The objective of this article is to examine the use of NSAIDs for attenuating exercise-induced muscle injuries (EIMI), with an emphasis on their safety and usefulness for improving muscle function and reducing soreness. NSAIDs are some of the most widely consumed medications in the world, and NSAID use as therapy for EIMI has increased dramatically over the last 20 years. However, there is a lack of agreement concerning NSAID effectiveness for this purpose. The lack of consensus about the efficacy of NSAID use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(16 citation statements)
references
References 88 publications
0
16
0
Order By: Relevance
“…On the other hand, if there is no secondary strength loss, more caution should be employed for such interventions because they might impair the recovery process. The results of our systematic review and meta-analysis may suggest why pharmacological, dietary, and therapeutic interventions have not been generally effective [23, 24], i.e., because there is minimal, if any, evidence for a secondary injury, at least not an injury resulting in an additional strength loss. This could be because the autogenetic and inflammatory phases may be constrained to lie within the initially damaged tissue and thus may be thought of as parts of the tissue repair and regeneration processes rather than degeneration processes that cause additional damage.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, if there is no secondary strength loss, more caution should be employed for such interventions because they might impair the recovery process. The results of our systematic review and meta-analysis may suggest why pharmacological, dietary, and therapeutic interventions have not been generally effective [23, 24], i.e., because there is minimal, if any, evidence for a secondary injury, at least not an injury resulting in an additional strength loss. This could be because the autogenetic and inflammatory phases may be constrained to lie within the initially damaged tissue and thus may be thought of as parts of the tissue repair and regeneration processes rather than degeneration processes that cause additional damage.…”
Section: Discussionmentioning
confidence: 99%
“…If the hypoalgesic mechanisms of ginger are predominantly peripheral, it is plausible that the oral dose given in the present study would require greater than 45 min to be absorbed, move to the peripheral site of injury (biceps) and exert an effect. While a single 5 mg/kg dose of caffeine has been shown to reduce exercise-induced muscle pain 60 min after administration (Maridakis et al, 2007), NSAIDS, which closely mimic the suggested pharmacological actions of ginger have not demonstrated a consistent hypoalgesic effect, with perhaps the best results occurring with prophylactic administration or chronic consumption over a several day period (Baldwin-Lanier, 2003;Connolly et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Among these substances, CK is considered the best indicator of a breakdown in muscle cell structure [174]. However, the substantial individual variability in CK responses to the same exercise bouts could reduce the usefulness as a biomarker of players' recovery status [178].…”
Section: E Biochemical Markers (Biomarkers)mentioning
confidence: 99%